A CFD Analysis and Aerodynamic Comparison of Two Silver Arrows - Ejresjö, Fredrik; Kange, Björn; Kjellström, David; Lindbäck, Mathias; Lundell, Stefan; Mybeck, Markus (My University, 2013)
During 1933 to 1939 the sport of racing was completely dominated by the German manufactures Auto Union (known today as Audi) and Mercedes-Benz. With their superior race cars (named Silver Arrows after their shining bodies and blistering acceleration) the German racing teams were victorious in most of the Grand-Prix races during this period. The cutting edge technologies in these cars remain a source of inspiration for new Mercedes-Benz and Audi cars to this day. The body shape of the Silver Arrows reveal that a great deal of time was spent optimizing the cars from an aerodynamic point of view, with the purpose of minimizing flow resistance. However, the term “downforce”, which is central to design of modern race cars, was relatively unknown. Compared to the modern use of powerful computers, the possibility of making flow calculations was also very limited at the time. In this project, two Silver Arrows (Auto Union Type C and Mercedes-Benz W25) have been analyzed from an aerodynamic point of view with the main purpose of calculating lift and drag force. No CADdata was available for the cars which is why they have been modeled from scratch. Two CMC-models of the cars, scaled 1:18 were used as a baseline. These were laser scanned at Volvo Cars. Curves for both cars have been extracted from the scanned data. With the profile curves as support, the bodies of the cars were modeled in CATIA V5 and from separate measurements the details of the cars were modeled. The final CAD-models were transferred to ANSA where initial surface meshes were generated. In STAR CCM+ high quality CFD-compatible surface meshes were generated. Volume meshes were then constructed and used in the simulations. The simulations were run with the boundary conditions rotating wheels and a moving ground at 80km/h. Pitch and yaw angels were set to 0⁰. The results of the simulation were analyzed and visualized using the post processing tools in STAR CCM+. The results of the simulations show that the Silver Arrows have good basic shapes from an aerodynamic perspective, but their design also include several drag-producing features and details. Both cars have little to no downforce, which was expected due to the lack of knowledge about the phenomenon at the time. Overall, the group is content with the result of the project and considers the objectives to be fulfilled. However, because of the emphasis on the pre processing, some planned parts needed to be excluded from the project. Originally, CFD-simulations were supposed to be performed in two different velocities. Also, wind tunnel testing of the CMC-models was to be carried out, and the obtained results were to be compared with the simulations. These parts would have contributed to a more thorough analysis of the Silver Arrows, why the project group recommends further tests and simulations.
Keywords: Energi; Grundläggande vetenskaper; Strömningsmekanik och akustik; Energy; Basic Sciences; Fluid Mechanics and Acoustics